1971
DOI: 10.1139/v71-469
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sulfoxides and Sulfones on the Temperature of Maximum Density of Water

Abstract: The influence of dimethyl sulfoxide (DMSO), diethyl sulfoxide (DESO), tetramethylene sulfoxide (TMSO), and tetramethylene sulfone (TMSO,) on the temperature of maximum density of water has been investigated. It is concluded that in dilute solution DESO stabilizes the characteristic three-dimensional structure of water. The other solutes, however, destabilize the structure of water over the entire concentration range studied (C1 .3 x mole fraction solute).L'influence du dimethyl sulfoxyde (DMSO), diethy1 sulfox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 8 publications
3
18
0
Order By: Relevance
“…For the three amino acids there is a linear dependence of Dh with molality in accordance with the behaviour predicted by Despretz equation. The behaviour exhibited by the amino acids is similar to that observed for electrolytes and some non-ionic solutes that disrupt water structure [2,3,5,8,9,11,30]. The slope of the plots of Dh vs. molality, corresponds to the Despretz constants.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…For the three amino acids there is a linear dependence of Dh with molality in accordance with the behaviour predicted by Despretz equation. The behaviour exhibited by the amino acids is similar to that observed for electrolytes and some non-ionic solutes that disrupt water structure [2,3,5,8,9,11,30]. The slope of the plots of Dh vs. molality, corresponds to the Despretz constants.…”
Section: Resultssupporting
confidence: 59%
“…To determine the temperature of maximum density for each amino acid solution, the experimental densities were plotted as a function of temperature. The curves obtained were fitted using the least-squares method to a parabolic equation [30], to determine the maximum of the curve which represents the temperature of maximum density for the aqueous solutions as can be observed in figure 4. Table 5 summarises the results for the temperature of maximum density obtained in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile to note here that while excess heats and volumes of mixing data confined to 26.5"C, whereas the present studies are confined to high temperature range (36-77°C). Therefore it may be concluded that the structural propensity of a solute as revealed by physical property is dependent on temperature and literature survey ( 1 2 , 1 3 ) indicates that structural interactions are sensitive to temperature and structure promoting interactions decrease with rise in temperature (14). The results of present study on water + cyclohexanone indicate that cyclohexanone loses its structure stabilizing character as temperature is increased and behaves as a structure breaker at higher temperature.…”
Section: Discussionmentioning
confidence: 52%
“…The shift in the temperature of maximum density (TMD) of water that occurs on dissolution of a solute is now recognized as a useful tool for the investigation of solute induced changes in the structure of liquid water (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, a number of recent papers (6,(10)(11)(12) suggest that some confusion exists as to the appropriate interpretation of the data.…”
Section: Introductionmentioning
confidence: 99%